2021
DOI: 10.1016/j.virusres.2021.198401
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of 10664 SARS-CoV-2 genomes to identify virus strains in 73 countries based on single nucleotide polymorphism

Abstract: Since the onslaught of SARS-CoV-2, the research community has been searching for a vaccine to fight against this virus. However, during this period, the virus has mutated to adapt to the different environmental conditions in the world and made the task of vaccine design more challenging. In this situation, the identification of virus strains is very much timely and important task. We have performed genome-wide analysis of 10664 SARS-CoV-2 genomes of 73 countries to identify and prepare a Single Nucleotide Poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…To date, a large number of single nucleotide polymorphisms (SNPs) in the SARS-CoV-2 genome have been identified by high-throughput sequencing [43] , [44] . However, the functions of these SNPs remain elusive.…”
Section: Resultsmentioning
confidence: 99%
“…To date, a large number of single nucleotide polymorphisms (SNPs) in the SARS-CoV-2 genome have been identified by high-throughput sequencing [43] , [44] . However, the functions of these SNPs remain elusive.…”
Section: Resultsmentioning
confidence: 99%
“…Another study conducted on 10,664 SARS-CoV-2 sequences from 73 countries found 107 SNPs. Based on this study, 5 SNPs are predicted to have a harmful impact, namely mutations T85I, Q57H, R203M, F506L, and S507C [28]. In addition, virus detection and epitope-based synthetic vaccine design require large amounts of genome analysis to find the most conserved parts so that global RT-PCR methods can be developed and used worldwide [29].…”
Section: Introductionmentioning
confidence: 99%